Cinematic rendering of pleural solitary fibrous tumor - Taha M Ahmed, MD; Elliot K. Fishman, MD (Radiology Case Reports)
Solitary fibrous tumors are rare and typically benign fibroblastic neoplasms with a mean age of onset ranging from 60 to 70 years. Solitary fibrous tumors may arise anywhere within the body, however the pleura is the most common site of origin for these tumors, with approximately 30% of tumors arising from the pleura. In this report we highlight the case of a 62-year-old woman who presented with gradually progressive left sided chest pain that was eventually diagnosed as a pleural SFT. We highlight the appearance of solitary fibrous tumor of the pleura on computed tomography and positron emission tomography imaging, as well as providing detailed cinematic rendering images of these rare neoplasms.